2022
DOI: 10.1016/j.gene.2021.146178
|View full text |Cite
|
Sign up to set email alerts
|

Gosha-jinki-Gan (GJG) shows anti-aging effects through suppression of TNF-α production by Chikusetsusaponin V

Abstract: Frailty develops due to multiple factors, such as sarcopenia, chronic pain, and dementia. Go-sha-jinki-Gan (GJG) is a traditional Japanese herbal medicine used for age-related symptoms. We have reported that GJG improved sarcopenia, chronic pain, and central nervous system function through suppression of TNF-α production. In the present study, GJG was found to reduce the production of TNF-α in the soleus muscle of senescence-accelerated mice at 12 weeks and 36 weeks. GJG did not change the differentiation of C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…K. et al found that CIN could reduce LPS-stimulated TNF-α production in RAW264.7 cells. [27] Qu, S. et al also confirmed that CIN decreased the level of proinflammatory cytokines, such as TNF-α, IL-1β and IL-6 in the activation of RAW264.7 cells, human macrophage-like cells U937, and primary peritoneal macrophages. [9] Toll-like receptors (TLR) play a key role in initiating congenital and inflammatory responses by detecting and scavenging pathogens or endogenous molecules.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…K. et al found that CIN could reduce LPS-stimulated TNF-α production in RAW264.7 cells. [27] Qu, S. et al also confirmed that CIN decreased the level of proinflammatory cytokines, such as TNF-α, IL-1β and IL-6 in the activation of RAW264.7 cells, human macrophage-like cells U937, and primary peritoneal macrophages. [9] Toll-like receptors (TLR) play a key role in initiating congenital and inflammatory responses by detecting and scavenging pathogens or endogenous molecules.…”
Section: Discussionmentioning
confidence: 85%
“…This result is in line with existing studies, for example, Hagihara. K. et al found that CIN could reduce LPS‐stimulated TNF‐α production in RAW264.7 cells [27] . Qu, S. et al also confirmed that CIN decreased the level of proinflammatory cytokines, such as TNF‐α, IL‐1β and IL‐6 in the activation of RAW264.7 cells, human macrophage‐like cells U937, and primary peritoneal macrophages [9] …”
Section: Methodsmentioning
confidence: 90%
“…Second, because follow‐up echocardiography was not available in a sufficient number of cases due to the retrospective nature of this study, we did not check the change in cardiac function, such as LVEF. Third, we could not compare the utility between RKT and other Kampo medicines, such as goshajinkigan, which has been shown to have an anabolic effect in several experimental studies [32,33]. However, considering the cardioprotective effect of ghrelin [14], we believe that RKT might have an advantage over goshajinkigan for the treatment of malnutrition in patients with HF.…”
Section: Discussionmentioning
confidence: 99%